Molecular dynamics simulation for studying the stability of structure H clathrate-hydrates of argon and large guest molecules. Issue 11 (2nd November 2018) - Reshadi, Pourya; Modarress, Hamid; Dabir, Bahram; Amjad-Iranagh, Sepideh
ABSTRACT: The aim of present paper is to study the stability of (argon + large guest molecules) structure H clathrate-hydrates by using molecular dynamics simulations and with employing the COMPASS force field to consider the molecular interactions. The simulations are performed by embedding the structure H clathrate-hydrates in a simulation cell under isobaric-isothermal ( NPT ) conditions. The obtained equilibrium lattice parameters are compared with the experimental data, where a good consistency is observed. The results show that the size and dipole moment of the guest molecules enclosed in the hydrate cages play the main role in the interactions between the guest molecules and the water molecules, which constitute the surrounding walls of the hydrate cage and these interactions would stabilize the hydrate structure. The characteristics of the clathrate-hydrate structure are analyzed by evaluating the radial distribution function, where the agreement between the results obtained in this work and other similar theoretical and experimental investigations validates the simulation procedure and related interpretations. GRAPHICAL ABSTRACT: